Karakterisasi Karakter Fisiologi Genotipe-Genotipe F2 Padi Ketan dengan Kemampuan Recovery Setelah Infeksi Tungro: Karakterisasi Karakter Fisiologi Genotipe-Genotipe F2 Padi Ketan dengan Kemampuan Recovery Setelah Infeksi Tungro - Ema Komalasari; Fitri Widiantini; Santika Sari; Nono Carsono (Universitas Bangka Belitung, 2019)
Tungro virus is one of the rice diseases which become one of limiting factors for rice production in Indonesia. The effective control can be done by using and rotation of resistant varieties. In order to develop tungro resistant varieties, hybridization has been conducted between susceptible (Ketonggo) and resistant variety (Utri Merah and ARC12596) i.e., Ketonggo x Utri Merah and Ketonggo x ARC12596. The main objective of the study was to characterize the physiological response of recovery genotypes group when compared to resistant genotypes. The genetic materials were F2 progenies of Ketonggo x Utri Merah and Ketonggo x ARC12596, each 230 genotypes. The experiment was conducted at BB Padi and Experimental Station of Faculty of Agriculture, Universitas Padjadjaran. Virus transmission was done using forced-tube inoculation method and symptoms scoring based on a standard evaluation system for rice. Traits observed were chlorophyll content, number of stomatal conductance, and quantum photosynthetic efficiency. The comparison of those traits between genotypes with recovery ability with those of resistant genotypes, susceptible genotypes, resistant variety check, and susceptible variety check was evaluated. It is found that recovered genotypes from both crossings did not show significant differences with those of resistant genotypes or resistant check variety on the above traits observed. Genotypes group with recovery ability can be used to suppress the spread of tungro disease.